2016
DOI: 10.1007/s00441-016-2431-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac fibrosis in myocardial infarction—from repair and remodeling to regeneration

Abstract: Ischemic cell death during a myocardial infarction leads to a multiphase reparative response in which the damaged tissue is replaced with a fibrotic scar produced by fibroblasts and myofibroblasts. This also induces geometrical, biomechanical, and biochemical changes in the uninjured ventricular wall eliciting a reactive remodeling process that includes interstitial and perivascular fibrosis. Although the initial reparative fibrosis is crucial for preventing rupture of the ventricular wall, an exaggerated fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
573
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 738 publications
(591 citation statements)
references
References 151 publications
(213 reference statements)
6
573
0
12
Order By: Relevance
“…Therefore, we speculate that tanshinone IIA may prevent ventricular remodelling by reducing the area of fibrosis. A previous study indicated that the ideal therapy for MI‐induced cardiac injury was to inhibit the reactive fibrosis (and other remodelling processes) as well as the regeneration of the infarct area in non‐infarcted areas 32. Tanshinone IIA suppresses cardiac fibrosis by regulating the paracrine factors released by cardiomyocytes that go on to activate the TGF‐b/Smads signalling pathway 9.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that tanshinone IIA may prevent ventricular remodelling by reducing the area of fibrosis. A previous study indicated that the ideal therapy for MI‐induced cardiac injury was to inhibit the reactive fibrosis (and other remodelling processes) as well as the regeneration of the infarct area in non‐infarcted areas 32. Tanshinone IIA suppresses cardiac fibrosis by regulating the paracrine factors released by cardiomyocytes that go on to activate the TGF‐b/Smads signalling pathway 9.…”
Section: Discussionmentioning
confidence: 99%
“…The Masson trichrome staining (Prabhu and Frangogiannis 2016; Talman and Ruskoaho 2016) showed a huge amount of tissues with fibrosis at border zones of rabbit hearts at postoperative 12 weeks given post‐MI inflammation (Anker and von Haehling 2004). An increase in cardiac fibrosis altered the constitutive relation of myocardium and further increased the ventricle wall shear, which impaired coronary vasculature (e.g., a vascular rarefaction) at border zones and contributed to the vicious cycle of ischemia and HF with time.…”
Section: Discussionmentioning
confidence: 99%
“…38 In this respect, LDE-MTX treatment led to a reduction in fibrosis in both subendocardial and interstitial areas, as documented by the local reduction of collagen I and III. Because fibrosis is stimulated by hypoxia and cell death, 39 the reduction of both by LDE-MTX accounted for the decrease in subendocardial fibrosis. Increase in VEGF expression by LDE-MTX was presumably involved in this effect.…”
mentioning
confidence: 99%